Do sme loans disbursed by banks impact on the performance of the sme sector in sri lanka? - Nuwan, A.N.; Bandara, H.G.K.N.; Ranasinghe, D.K.; Perera, D.A.M.; Bulankulama, S.W.G.K. (University of Jaffna, 2022)
Purpose: The SME sector is widely accepted as a seedbed for entrepreneurs in providing various socio-economic objectives and long-term economic development. According to the recent survey conducted by the European Commission, small and medium-sized enterprises (SMEs) are highly dependent on bank loans when it comes to financing their activity and accomplishing their growth ambitions. This study attempted to identify the effectiveness of SME loans disbursed by banks on the performance of SME sector in Sri Lanka. Methodology: The study is more towards exploratory design with a deductive approach which attempts to provide insights with a deeper understanding. The study used archival research technique by means of secondary data from 2008 to 2020 published in annual reports and other accepted secondary sources. Findings: The results from this study indicated that loans obtained by SMEs from banks have a positive significant impact on the growth of SME sector in Sri Lanka. In 2019, SME sector, more than 60% of the loan amount was absorbed from the total loan disbursement provided by banks. The results further revealed that loans provided by banks have a positive impact on sales growth which is statistically significant and the annual interest rate offered by the private banks significantly impacts the demand for SME loans. The results also indicated that a high-interest rate can cripple the expansion of SMEs in the Sri Lankan market. Overall SMEs' demand for new loans increased constantly throughout the analyzed period with a slight fall in 2010 and 2011. Research limitations: Secondary data may be incomplete and lack of accuracy is the key limitation of this study. Moreover only 12 years data were considered due to unavailability of data on SME sector in Sri Lanka. Implications: The paper recommended that maintaining single-digit interest rates by private and state banks is beneficial for SME sector growth. Fiscal institutes should follow an artificial intelligence model to evaluate borrowings and repayment of SMEs. Loans disbursed to the SME sector by banks impact to enhance the volume of the total turnover of SMEs. Hence expansion and establishing business resilience of the SME sector which has more than 70% of establishments of the country is a timely need.
Keywords: Loan disbursement; SME; Banking sector; SME performance